Consumer acceptance of cultured meat: A systematic review. (September 2018) - Bryant, Christopher; Barnett, Julie
Abstract: Cultured meat grown in-vitro from animal cells is being developed as a way of addressing many of the ethical and environmental concerns associated with conventional meat production. As commercialisation of this technology appears increasingly feasible, there is growing interest in the research on consumer acceptance of cultured meat. We present a systematic review of the peer-reviewed literature, and synthesize and analyse the findings of 14 empirical studies. We highlight demographic variations in consumer acceptance, factors influencing acceptance, common consumer objections, perceived benefits, and areas of uncertainty. We conclude by evaluating the most important objections and benefits to consumers, as well as highlighting areas for future research.